The Role of Balanced Nutrition in Improving the Immune System: A Literature Study - Firayani, Firayani (Journal Nutrizione, 2024)
Amidst the flow of globalization, modern lifestyles characterized by high mobility, instant diets, and chronic stress exposure have had a significant impact on the decline in the quality of community immunity. This study aims to critically examine the relationship between balanced nutrition and the immune system through a qualitative literature study approach. Analysis was conducted on 40 primary scientific sources from accredited national and international journals, as well as policy documents and reports from global institutions such as WHO and FAO in the period 2015–2025. The results of the study indicate that adequate intake of macro and micro nutrients, especially vitamins D, C, A, E, zinc, and selenium, plays an important role in maintaining the integrity and responsiveness of the body's immune system. The findings also show that deficiencies of essential nutrients contribute to decreased vaccine effectiveness, increased risk of respiratory tract infections, and weakened resistance to non-communicable diseases. However, the gap between knowledge and practice of nutritious food consumption is still high, especially in the lower middle economic group. Therefore, balanced nutrition is not only an individual health issue, but also a structural problem that requires cross-sectoral solutions. This study recommends the integration of nutritional policies based on scientific evidence, as well as public education based on cultural contexts to strengthen the community's immune system in a sustainable manner